Concurrent Community Transmission of Enterovirus D68 With Human Rhinoviruses and Respiratory Syncytial Virus Among Children in Sendai, Japan. Issue 5 (May 2018) - Metoki, Takaya; Okamoto, Michiko; Suzuki, Akira; Kitaoka, Setsuko; Miyabayashi, Hiroki; Rokugo, Yuka; Onuma, Ryoichi; Noguchi, Rie; Sato, Taiki; Watanabe, Yohei; Ohmiya, Suguru; Sato, Ko; et al.
Abstract : Background: In the autumn of 2015, we experienced a surge in the number of pediatric cases of wheeze in our hospital, which was suspected to be caused by enterovirus (EV)-D68 transmission in the community. Thus, we implemented an ad hoc retrospective surveillance for EV-D68. Methods: Patients <15 years of age with acute respiratory infection were eligible for inclusion in this study. All enrolled patients underwent virus detection test. Additionally, neutralization tests (NTs) were performed using the stored serum samples of the enrolled patients to compare the antigenicity of the virus isolated in this study with that isolated in 2010 and evaluate the anti-EV-D68 antibody prevalence. Results: Respiratory syncytial virus (RSV) was the most commonly detected virus (35%), followed by EV-D68 (19%) and non-EV-D68 enteroviruses/human rhinoviruses (14%). Patients with EV-D68 infection had higher median age than those with RSV infection ( P < 0.05). Moreover, patients with EV-D68 infection showed a higher expiratory wheeze prevalence than those with non-EV-D68 enterovirus/rhinovirus and RSV infections. The antigenicity of the isolate from the current study was similar to the virus that circulated in 2010. At the early study phase, children in our community did not have high NT titers, but the median log NT titer increased from 1.5 to 5 over time ( P < 0.05). Conclusion: This study showed the concurrent circulation of EV-D68 with non-EV-D68 enteroviruses/rhinoviruses and RSV in infants and children in our community and captured the early stage of EV-D68 transmission.